EFEKTIVITAS PENERAPAN SONIC BLOOM DAN TANAMAN REFUGIA DALAM MENINGKATKAN PERTUMBUHAN DAN HASIL SAWI HIJAU (Brassica juncea L.) - Imam Hartono Bangun; Asritanarni Munar; Wan Arfiani Barus; Dedi Kurniawan (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The study was to examine the application of sonic bloom and refugia plants to increase growth and yield of mustard greens (Brassica juncea L.). This study used a Factorial Time Series Randomized Block Design (FTSRBD) with 3 replications. The application factor of refugia plants (R) are 3 levels: R0 = control, R1 = Ocimum basilicum, and R2 = Zinnia elegans with different locations consisting of (S0) = no sound, (S1) = heavy metal music with a frequency of 21 -14000 Hz and (S2) = classical music sound with a frequency of 21-13500 Hz. Data analysis was continued according to Duncan's Multiple Range Test (DMRT) at a 5% confidence level.  The results showed that the application of sonic bloom with classical music influenced plant growth and yield through parameters of plant height, number of leaves, leaf area, number of chlorophyll and number of stomata. Refugia plants with the type of plant O. basilicum affect the growth and yield of plants through the number of leaves parameter. The application of sonic bloom with rock music affects the growth and yield of plants through parameters of pest attack intensity. The interaction of sonic bloom application and refugia plants did not have a significant effect on the observed parameters measured.